Retropharyngeal lymph node metastasis on N stage of nasopharyngeal carcinoma - Pan, Xin-Bin (PLoS One, 2021)
PURPOSES: To evaluate retropharyngeal lymph node metastasis on N stage of nasopharyngeal carcinoma (NPC). METHODS: NPC patients were extracted from the Surveillance, Epidemiology, and End Results database between 2004 and 2016. Pathologically confirmed patients with complete data of retropharyngeal lymph node metastasis were investigated. The included patients were divided into N1a and N1b groups. Overall survival (OS) and cancer-specific survival (CSS) were assessed using the Kaplan–Meier method and propensity score matching (PSM) analyses. RESULTS: This retrospective cohort study examined 759 patients: 70 who were stage N1a and 689 who were stage N1b. Before PSM, N1a group was associated with similar 5-year OS (77.7% vs. 72.4%; P = 0.15) and CSS (85.6% vs. 79.9%; P = 0.09) compared to N1b group. After PSM, a similar OS (75.0% vs. 60.7%; P = 0.12) was found between the radiotherapy and chemoradiotherapy groups. However, N1a group showed a better 5-year CSS (83.8% vs. 71.1%; P = 0.04) compared to N1b group. Stage N1b was an independent risk prognostic factor for CSS (hazard ratio = 2.54, 95% confidence interval: 1.02–6.34; P = 0.04). CONCLUSIONS: OS was not different between N1a and N1b groups. Retropharyngeal lymph node metastasis defined as stage N1 of the 8(th) edition American Joint Committee on Cancer staging system is reasonable.